The Effect of Compensation and Work Stress on Employee Performance in the Sales Force Section of PT. World Innovative Telecommunication Makassar - Nurhaliza; Muhammad Ilham Wardhana Haeruddin; Zainal Ruma; Abdi Akbar; Uhud Darmawan Natsir (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of compensation and work stress on the performance of sales force employees at PT. World Innovative Telecommunication Makassar. The sample in this study were 100 sales force employees (promoters). The data used were primary data and secondary data obtained from distributing questionnaires. The results of this study indicate that there is a positive influence between the compensation variable (X1) on employee performance (Y) and there is a negative effect between the work stress variable (X2) on employee performance variables which can be shown through the multiple linear regression equation, namely Y = 11.104 + 1.241 X1 – 0.147 X2 and has a significant effect on the tcount value of each variable of 13.855 > t table (X1) and -2.055 > t table (X2), with a significance level of 0.000 <0.05 (X1) and 0.043 <0.05 ( X2). The R Square value of 0.657 indicates that the compensation variable and work stress variable in this study contributed 65.7%, while 34.3% was explained by causes and other factors.